2016
DOI: 10.1074/jbc.m115.686170
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis δ Factor Functions as a Transcriptional Regulator by Facilitating the Open Complex Formation

Abstract: Most bacterial RNA polymerases (RNAP) contain five conserved subunits, viz. 2␣, ␤, ␤, and . However, in many Grampositive bacteria, especially in fermicutes, RNAP is associated with an additional factor, called ␦. For over three decades since its identification, it had been thought that ␦ functioned as a subunit of RNAP to enhance the level of transcripts by recycling RNAP. In support of the previous observations, we also find that ␦ is involved in recycling of RNAP by releasing the RNA from the ternary comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 37 publications
0
27
0
Order By: Relevance
“…Indeed, it has been reported that δ and σ A can bindsimultaneously to core RNAP, with negative cooperativity (51). However, other experiments indicated mutual exclusion of the binding of δ and σ A to core RNAP (43,52).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Indeed, it has been reported that δ and σ A can bindsimultaneously to core RNAP, with negative cooperativity (51). However, other experiments indicated mutual exclusion of the binding of δ and σ A to core RNAP (43,52).…”
Section: Resultsmentioning
confidence: 92%
“…Importantly, δ has a complex effect on transcription. It inhibits initiation from weak promoters mediated by σ A (41,42), stimulates or inhibits transcription from certain other promotors (43,44) and increases RNAP recycling speed (42,43) in synergy with the DNA helicase HelD (45), probably by dissociation of stalled RNAP-DNA or RNAP-RNA complexes. Transcriptomics experiments indicate δ reduces non-specific initiation of transcription which is relatively prevalent in Gram positive bacteria (46,47).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In support of this, those sigma factors that have increased binding to RNAP upon deletion ( S in E. coli [24], B / F in cyanobacteria [25], and B in S. aureus) are all major components of the general stress response in their respective organism (45)(46)(47)(48)(49). Furthermore, as with factors, the release of ␦ from RNAP has the potential for profound alterations in gene expression, as a recent publication demonstrates the ability of ␦ to selectively affect individual promoters (7,8) via binding to specific promoter elements (50). As the disruption of rpoE results in slower bacterial growth in a variety of organisms (e.g., an extended lag phase [8,51,52]), removal of this subunit from RNAP may actually present a survival advantage during stress, redirecting resources away from division and toward repair and cellular maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we have included the RNA polymerase-interacting protein HelD and the nonessential delta subunit (RpoE). HelD binding stimulates transcription in an RpoE-dependent manner, suggesting that these two accessory proteins are important to allow rapid growth (59,60). Interestingly, both proteins are absent from the rather slowly growing M. mycoides strain JCVI-syn3.0.…”
Section: Transcriptionmentioning
confidence: 99%